Models of adaptive management under changing economic conditions in the real estate market - MYKYTCHENKO, Bohdan (Ways to Improve Construction Efficiency, 2025)
Adaptive management under volatile economic conditions is becoming a decisive factor for the development sector, where long investment cycles, high risks, and dependence on external factors converge. The growing economic turbulence, currency fluctuations, inflationary pressures, and regulatory transformations create an environment in which conventional management models lose their effectiveness. Adaptability emerges not only as a survival mechanism but also as a strategic development tool that ensures resilience, flexibility, and rapid managerial responsiveness. The essence of the adaptive approach lies in the continuous adjustment of actions, strategies, and processes in accordance with the changing external environment. In the field of real estate development, this model integrates digital technologies, business analytics, forecasting, and scenario planning. The foundation of modern adaptive architecture is the integration of information systems – BIM, ERP, CRM, and Business Intelligence – which provide end-to-end control over financial, technical, and operational processes. As a result, management acquires a proactive nature focused on preventing deviations rather than eliminating their consequences. Economic instability generates the need for flexible decision-making systems based on analytical instruments such as GAP, FMEA, and PESTEL analyses. These methods help identify strategic gaps, anticipate critical risks, and forecast external influences, forming a multilevel adaptation framework. In combination with digital KPI dashboards, they create a structure of adaptive controlling that records key performance indicators in real time, ensures informational feedback, and enhances managerial transparency. The effectiveness of adaptive management depends not only on technological advancement but also on an organization’s readiness for internal transformation. Flexible management systems require decentralization of decision-making, delegation of authority, transformation of corporate culture, and the implementation of Agile and Lean Construction principles. This approach minimizes institutional barriers, accelerates communication, and shortens the time lag between risk detection and managerial response. The development of adaptive models in the real estate business enables the integration of big data analytics, artificial intelligence, and machine learning to build predictive models that account for changing demand, resource costs, and macroeconomic parameters. Systematic implementation of these approaches shapes a new management paradigm – dynamic, analytically grounded, and digitally integrated. Adaptive management in real estate development transforms the very logic of strategic thinking: from reactive responses to anticipatory forecasting, from fixed plans to variable scenarios, from intuitive decisions to data-driven analytical models. As a result, companies gain the ability not only to maintain stability under crisis conditions but also to turn market fluctuations into a catalyst for innovative growth, creating new competitive advantages in the global environment.